2021
DOI: 10.3390/diagnostics11122299
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Supply Chain Management Systems for Point of Care Diagnostic Services: Optimising COVID-19 Testing Capacity in Resource-Limited Settings

Abstract: Background: Point of care (POC) testing has enabled rapid coronavirus disease 2019 (COVID-19) diagnosis in resource-limited settings with limited laboratory infrastructure and high disease burden. However, the accessibility of the tests is not optimal in these settings. This scoping review mapped evidence on supply chain management (SCM) systems for POC diagnostic services to reveal evidence that can help guide future research and inform the improved implementation of SARS-CoV-2 POC diagnostics in resource-lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…This study was guided by results of a scoping review. 12 Following the scoping review, we propose a multiphase mixed-method study, which will be implemented in three phases. The results of the scoping review revealed that for the continuum of POC diagnostic services, POC diagnostic tests must be available and accessible to all who need them through a sustainable SCM system which is a multi-faceted system influenced by several factors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study was guided by results of a scoping review. 12 Following the scoping review, we propose a multiphase mixed-method study, which will be implemented in three phases. The results of the scoping review revealed that for the continuum of POC diagnostic services, POC diagnostic tests must be available and accessible to all who need them through a sustainable SCM system which is a multi-faceted system influenced by several factors.…”
Section: Methodsmentioning
confidence: 99%
“…12 The scoping review also revealed that there is limited published research on SCM of POC diagnostic services in resourcelimited settings and that there are currently no primary studies on the SCM systems of COVID-19 POC diagnostic services. 12 In phase 1, we will perform a geospatial analysis to investigate the spatial distribution of COVID-19 testing services. In phase 2, we will perform an audit of POC diagnostic services including its supply chain to evaluate the effect of SCM on accessibility of COVID-19 POC diagnostics services and reveal SCM barriers and enablers of accessibility of COVID-19 POC diagnostic services.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the contributing factors for equitable accessibility, distribution and availability of POC tests is the agility of supply chain management systems. Maluleke et al, 2021, conducted a scoping review to systematically map evidence on supply chain management systems for POC diagnostics services with a focus on optimising the SARS-CoV-2 testing capacity in resource-limited settings [ 7 ]. The results of the review showed has showed that there is limited research evidence on POC diagnostics supply chain management systems globally.…”
mentioning
confidence: 99%